Online Information Beheviour Of Faculty And Students Of The National Film And Television Institute (Nafti) During The Covid-19 Pandemic - Koranteng, E.O. (University Of Ghana, 2021)
The emergence of COVID-19 has affected all spheres of human life globally. In higher education across the globe, the outbreak of COVID-19 saw a lot of universities move away from face-to-face to online teaching which may have effect on the information behaviour of faculty and students in universities. The study therefore employed a survey research method and a quantitative research approach to investigate the online information behaviour of faculty and students of the National Film and Television Institute (NAFTI) during the COVID-19 pandemic. Questionnaire was used as instrument for data collection. The study employed census approach to survey the entire available population, comprising of 33 faculty members and 284 students, for a total of 317 targeted respondents for the study. The study found that the pandemic has increased the frequency at which faculty and students access information online as they spent more hours online than before the pandemic. Health information was the most mentioned new information need mentioned by faculty and students during the COVID-19 pandemic. Both faculty and students relied mostly on search engines to access and retrieve work/academic and health related information during the pandemic. The faculty relied heavily on social media, with over 90% using this medium for health information to meet their needs. The study also revealed that most of the respondents were not able to apply most online information retrieval skills and evaluation techniques. The main challenges that hinder the respondents’ ability to access the relevant information online during the pandemic were lack of training, slow internet connection and cost of data bundles among others. The study recommended among others that the NAFTI library should organize training and assistance to faculty and staff to enhance their information retrieval skills, market its available resources and that management of NAFTI and the Ghana government should take steps to make internet widely accessible at a lower cost.
MPhil. Information Studies
Keywords: National Film And Television Institute (Nafti); Covid-19 Pandemic